INHIBITION OF CALCIUM OXALATE CRYSTALLIZATION CAUSING KIDNEY STONES IN VITRO BY AN EXTRACT OF Bluméa balsamifera - Nguyen Pham Tuan; Bang Hong Lam; Nguyen Pham Tu; Le Thao Nguyen; Tran Duc Tai (Tạp chí Khoa học Đại học Đà Lạt)
The inhibitory effect of Bluméa balsamifera extract on the nucleation, growth, and aggregation phases of calcium oxalate formation has been studied. Plant samples were extracted by the maceration method with 80.00% ethanol. The results showed that the moisture content of Bluméa balsamifera extract was 82.83% and the yield was 5.79%. Bluméa balsamifera extract contains bioactive compounds including alkaloids, flavonoids, saponins, terpenoids, tannins, and phenol. Bluméa balsamifera extract has the ability to inhibit the nucleation of calcium oxalate with an IC50 value of 4.25 mg/ml. Bluméa balsamifera extract has a significant inhibitory effect on the growth of calcium oxalate crystals with an IC50 value of 2.99 mg/ml. Finally, Bluméa balsamifera extract is capable of inhibiting the aggregation of calcium oxalate with an IC50 value of 2.56 mg/ml.